Synthesis of Micheliolide Derivatives and Their Activities against AML Progenitor Cells - Yue Chen; Quan Zhang; Jing Long; Qian-Qian Shi; Ya-Hui Ding; Wei-Wei Ma (Molecules, 2013)
Micheliolide (MCL) derivatives with etherification or esterification of the hydroxyl group at the C4 position were synthesized and evaluated for their activities against different acute myelogenous leukemia (AML) cell lines. These derivatives demonstrated comparable activities against AML cell lines HL-60 and doxorubicin resistant cell line HL-60/A. As to multi-drug resistant AML progenitor cells KG-1a, MCL and some of its derivatives maintained significant activities, and only 1.1–2.7 fold activity reductions were observed when compared with the activities against HL-60, while doxorubicin showed 20-fold activity reduction. Our study demonstrated that the C4 hydroxyl group of MCL might not only be a suitable position for structural modifications, but also be a starting point for the design of appropriate molecular probes to explore the specific targets in the progenitor cell line KG-1a.